Microbiological Research and Applied Sciences in the North Eastern Region of India - Datta, Sibnarayan; Chattopadhyay, Pronobesh (Defence Life Science Journal, 2020)
The northeastern part of India (NE India) is an important biodiversity hotspots and is blessed with a huge diversity of flora and fauna along with other natural resources. Being quite distinct in natural features from rest of the country, NE India has its own unique challenges and opportunities. This part of India is geographically isolated from China by Eastern Himalayas, while tropical forests separate this region from Myanmar and Bangladesh. The armed forces deployed in the NE region have to operate in a wide variety of environments ranging from high altitudes, to tropical rain forests, which pose several operational challenges.